Structural design and fabrication of a go-kart front suspension - Syahriza, Muhammad Irfan; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The suspension system is an essential component of an automotive vehicle, ensuring proper functionality and performance. It absorbs shocks from rough terrains while maintaining handling stability by keeping all tyres in contact with the road. This project focuses on developing a functional front suspension for a go-kart. The most suitable suspension type will be selected and integrated into the go-kart's frame. An informed decision will be made through mock-ups and testing of different suspension types. Ultimately, this research and development process will enhance the go-kart's overall performance.